2019
DOI: 10.17755/esosder.428802
|View full text |Cite
|
Sign up to set email alerts
|

Yalin Alti Si̇gma:bi̇r Pet Şi̇şi̇rme Maki̇nasinda Süreç İyi̇leşti̇rme Uygulamasi

Abstract: ÖzGünümüzde yaşanan küresel rekabet ortamında faaliyetlerini sürdürebilmek ve rekabet gücünü artırmak için pek çok firma müşterilerine en iyi kalitede en düşük maliyet ile tam zamanında hizmet veya ürün sunma konusunda pek çok geliştirici yöntemlere başvurmaktadırlar. Bu çabaların bir büyük bölümü, işletmelere finansal ve müşteri memnuniyeti şeklinde kazanımlar sağlayan değer katmayan işletme süreçlerinin iyileştirilmesi üzerinde odaklanmıştır. 2000'li yıllardan sonra ortaya çıkan ve işletmelerin süreçlerini i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Avunduk (2019) performed a process improvement on the pet blow molding machine using the Lean Six Sigma method. This work and financial gain contributed to the company's long-term environmental sustainability goal and the vision of a more livable world with less energy consumption [6]. Sevgili and Antmen (2019) aimed at lean production by using value stream mapping in a metal processing factory and minimized intermediate stocks due to process improvement, shortened the production flow time, and increased the daily production amount [7].…”
Section: Introductionmentioning
confidence: 99%
“…Avunduk (2019) performed a process improvement on the pet blow molding machine using the Lean Six Sigma method. This work and financial gain contributed to the company's long-term environmental sustainability goal and the vision of a more livable world with less energy consumption [6]. Sevgili and Antmen (2019) aimed at lean production by using value stream mapping in a metal processing factory and minimized intermediate stocks due to process improvement, shortened the production flow time, and increased the daily production amount [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the researcher observed that LSS is also used in critical issues such as the development of data-based process management systems. Avunduk (2019) performed a process improvement application by following the DMAIC stages in a study in which a company operating in the beverage bottling industry applied LSS techniques to reduce energy use in its production processes. Within the scope of this particular study, the maximum energy consumption point was determined by analyzing energy usage, and due to the project-oriented nature of LSS, the entire application was performed on the PET bottling process, which consumes the most energy.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou ve ark., [12] plastik enjeksiyon kalıplarında soğutma sisteminin otomatik yerleşimine yönelik bir çalışma yapmıştır. Avunduk, ve ark., [13] pet şişirme makinelerinde farklı yöntemlerle iyileştirme süreci, Brandau, [14] enjeksiyon şişirme makinelerinin donanımı, Bayram ve ark., [15] şişirme makinelerinde fırın optimizasyonu üzerine çalışmalar yapmıştır. Plastik enjeksiyon alanında yapılan birçok çalışma, üretim verimliliğini arttırmak adına soğutmayı iyileştirerek döngü süresinin (cycle time) en aza indirilmesine odaklanmıştır.…”
Section: Introductionunclassified